Morphological, mechanical and thermo-kinetic characterization of coal ash incorporated high performance PEO/PMMA thin film electrolyte composites. (16th November 2017) - Sultana, Sabiha; Khan, Mohammad Saleem; Rehan, Imran; Rehan, Kamran; Amin, Noor-ul-; Humayun, Muhammad; Tabassum, Safia; Minhaz, Aaliya
Abstract: In the present work indigenous coal ash of Pakistan was used to prepare polymeric nanocomposites with Poly (ethylene oxide) (PEO)/Poly (methyl methacrylate) (PMMA)/lithium perchlorate (LiClO4 ). The coal ash was first characterized by various advanced spectroscopic techniques. The coal ash loading into the polymeric blend composites was considered by Thermo gravimetric/differential thermal analysis (TG/DTA), universal testing machine (UTM) and scanning electron microscopy (SEM)/energy dispersive x-rays (EDX) analysis. From TG/DTA data detailed kinetic analysis was performed. By applying various kinetic models, a range of kinetic parameters like ▵ E, ▵ G, ▵ H, ▵ S and A were successfully calculated for the first time for the studied system. Based upon aforementioned characterization it was established that coal ash incorporation into the polymeric blend composites improves its thermal and mechanical performance.